The Relationship between Maternal Knowledge and Attitude and Compliance with Basic Immunization in Infants 0-12 Months - Viony Ersantyas Rosanery; Supratman Supratman (GLOBAL HEALTH SCIENCE GROUP, 2024)
Since 1956, the Indonesian public health program has carried out a health program, namely immunization. Immunization is a government health measure that has been proven effective in overcoming six diseases that can affect children, namely : tuberculosis, diphtheria, pertussis, measles, tetanus, and polio. The Indonesian Ministry of Health stated that in December 2023 and January 2024 there were cases of poliomyelitis or exposure to the VDPV TYPE 2 virus. The level of knowledge, attitude and compliance of mothers is very important for the provision of immunizations routinely to their children. Objective to observe the relationship between maternal knowledge and attitudes and compliance with basic immunization in infants 0-12 months at the Kartasura Health Center. This research is included in the quantitative type and the information is measured using a questionnaire measuring tool. This research is cross-sectional and data collection is obtained by purposive sampling. The community involved were as many as 93 mothers who had babies aged 0-12 months who came to the Kartasura Health Center. The level of knowledge, attitude and compliance of mothers is measured by the knowledge, attitude and practice questionnaire (KAP). In addition, the KAP instrument has been tested for reliability and validity, Cronbach's alpha coefficient was found to be 0.703. This questionnaire was made to assess the role of the following parameters to understand the knowledge, attitudes and practices (KAP) of mothers regarding basic immunization such as filling in maternal demographic data, age of the child, how many children to be to, name of the vaccine given, vaccine dose, continuing vaccination after immunization reaction, adhering to the immunization schedule. The findings showed that as many as 83 respondents (62.9%) had strong knowledge in basic immunization, 72 respondents (54.5%) had a good attitude towards basic immunization, while 75 respondents (51.8%) had good adherence to basic immunization. The results of the p value of 0.2373 were obtained, the results of the study stated that there was no relationship between the level of basic immunization knowledge and compliance with the administration of basic immunization in infants at the Kartasura Health Center. In addition, in the Kartasura Health Center, there was a correlation, related to the p value of 0.0005, between attitudes towards basic immunization and compliance with the administration of basic immunization to newborns.